Activated Platelets Induce an Anti-Inflammatory Response of Monocytes/Macrophages through Cross-Regulation of PGE2 and Cytokines. (16th May 2017) - Linke, Bona; Schreiber, Yannick; Picard-Willems, Bettina; Slattery, Patrick; Nüsing, Rolf M.; Harder, Sebastian; Geisslinger, Gerd; Scholich, Klaus
Abstract : Platelets are well known for their role in hemostasis and are also increasingly recognized for their roles in the innate immune system during inflammation and their regulation of macrophage activation. Here, we aimed to study the influence of platelets on the production of inflammatory mediators by monocytes and macrophages. Analyzing cocultures of platelets and murine bone marrow-derived macrophages or human monocytes, we found that collagen-activated platelets release high amounts of prostaglandin E2 (PGE2 ) that leads to an increased interleukin- (IL-) 10 release and a decreased tumor necrosis factor (TNF) α secretion out of the monocytes or macrophages. Platelet PGE2 mediated the upregulation of IL-10 in both cell types via the PGE2 receptor EP2. Notably, PGE2 -mediated IL-10 synthesis was also mediated by EP4 in murine macrophages. Inhibition of TNF α synthesis via EP2 and EP4, but not EP1, was mediated by IL-10, since blockade of the IL-10 receptor abolished the inhibitory effect of both receptors on TNF α release. This platelet-mediated cross-regulation between PGE2 and cytokines reveals one mechanism how monocytes and macrophages can attenuate excessive inflammatory responses induced by activated platelets in order to limit inflammatory processes.